The Oxidoreductase DsbA1 negatively influences 2,4-diacetylphloroglucinol biosynthesis by interfering the function of Gcd in Pseudomonas fluorescens 2P24 - Zhang, Bo (BMC Microbiol, 2020)
BACKGROUND: The polyketide antibiotic 2,4-diacetylphloroglucinol (2,4-DAPG), produced by Pseudomonas fluorescens 2P24, is positively regulated by the GacS-GacA two-component system. RESULTS: Here we reported on the characterization of DsbA1 (disulfide oxidoreductase) as novel regulator of biocontrol activity in P. fluorescens. Our data showed that mutation of dsbA1 caused the accumulation of 2,4-DAPG in a GacA-independent manner. Further analysis indicated that DsbA1 interacts with membrane-bound glucose dehydrogenase Gcd, which positively regulates the production of 2,4-DAPG. Mutation of cysteine (C)-235, C275, and C578 of Gcd, significantly reduced the interaction with DsbA1, enhanced the activity of Gcd and increased 2,4-DAPG production. CONCLUSIONS: Our results suggest that DsbA1 regulates the 2,4-DAPG concentration via fine-tuning the function of Gcd in P. fluorescens 2P24.